“MYCO SYNTHESIS OF SILVER NANOPARTICLES USING GLIOCLADIUM ROSEUM (CLONOSTACHYS ROSEA (LINK) SCHROERS, SAMUELS) AND ITS ANTIMICROBIAL EFFICACY AGAINST SELECTED PATHOGENS” - NAIR, BHARATH; ABRAHAM, DELMY; DINESH, AMRITA; SWAMY, G. E. MALLIKARJUNA (International Journal of Current Pharmaceutical Research, 2020)
Objective: Antimicrobial efficacy of silver nanoparticles from Gliocladium roseum, culture filtrate (C. F.) and mycelial mat extract (M. E.) against selected pathogens. Methods: Culture filtrate (C. F.) and Mycelial mat extract (M. E.) of Gliocladium roseum were subjected to 10 Mm silver nitrate solution for the synthesis of silver nanoparticles. Formed silver nanoparticles were evaluated via UV-vis spectroscopy and the structural elucidation was done by FT-IR and TEM. Antimicrobial efficacy was tested against bacterial (Salmonella typhi and Klebsiella pneumonia) and fungal (Cladosporium cladosporioides and Alternaria alternata) pathogens. Different nanoparticle concentrations-50, 100, 150 and 200 µl were checked via disc diffusion method. Results: Gliocladium roseum (C. F. and M. E.) on interaction with silver nitrate solution effectively reduced metallic silver exhibiting a colour change from yellow to dark brown within 24 h due to the formation of silver nanoparticles. The UV-vis spectrum of C. F. and M. E. showed maximum absorption peaks at 350-400 nm and 400-450 nm respectively and FT-IR and TEM showed strong N-H bonding and spherical shaped silver nanoparticles with the size of 11-19 nm (C. F.) and 25-38 nm (M. E.). Antimicrobial analysis resulted in efficient inhibitory activity against Salmonella typhi, Klebsiella pneumonia and also showed moderate inhibitory activity against Alternaria alternata and Cladosporium cladopsorioides. Conclusion: The synthesis of silver nanoparticles from fungus Gliocladium roseum is simple, cheap, safe and eco-friendly thus emphasising on large scale scientific application.